Proyecto de factibilidad para la creación de una empresa productora de insecticida orgánico en base a la hoja de tabaco y su comercialización en el cantón Sozoranga, provincia de Loja - Jaramillo Temay, Ruth Elizabeth (2015)
This feasibility project aimed to create a "FEASIBILITY PROJECT FOR THE CREATION OF AN ORGANIC INSECTICIDE PRODUCTION COMPANY BASED ON SNUFF SHEET AND MARKETING IN CANTON Sozoranga, Loja province.". To meet this goal was necessary to use inductive methods - Deductive, Analytic - Synthetic, Mathematical and Statistical and techniques of observation and survey which was applied to a sample of 334 household surveys Canton Sozoranga to determine demand and a survey of agricultural stores Canton 5 to determine the offering, may determine the existing unsatisfied demand was 98,023 liters of insecticide. The project has an installed capacity of 23,976 liters of insecticide and work for the first year with an installed capacity of 80% or 3596 bottles of 5 liters capacity insecticide company will operate in the neighborhood Spain, via New Fatima located in the canton Sozoranga . Moreover, the Company will comply as limited liability and bear the name and address of: Ecotierra CIA. LTDA. "The investment required for the implementation of the project is $ 47,595.28, the cost of each freshener was estimated at $ 24.90, so the profit margin of 30% was established, which the sale price of 5 liters of insecticide is $ 32.18. The project is feasible and realizable as evidenced by the financial indicators such as NPV was worth 19481.7, the IRR was calculated at 20.65%. The initial investment will be recovered in three years eight months and 22 days and the cost benefit ratio indicates that you will get 0.30 cents for every dollar invested, while using sensitivity analysis can establish that the project supports up 20.42 % increase in costs and 15.71% decrease in revenue. Once the work is completed it can determine the most important conclusions were: The project is welcome as it proves it all studies. Finally among the important recommendations it is that the project implementation is recommended due to the results obtained from the evaluation criteria developed in this study, and periodically review the market and trends in order to prepare for the changes they can present to introduce new services to be better meet the needs of customers.